#### Answer

$(y-1)^2(4x+5)(x+5)$

#### Work Step by Step

Given $4x^2(y-1)^2+25x(y-1)^2+25(y-1)^2 = (y-1)^2(4x^2+25x+25) = (y-1)^2(4x^2+20x+5x+25) = (y-1)^2[4x(x+5)+5(x+5)] = (y-1)^2(4x+5)(x+5)$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$(y-1)^2(4x+5)(x+5)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.